A Recycling and Measurement of Floodwater Using Arduino, Potassium Alum and River Stone - Yusop, Noorrezam; Safie, Nur Ezyanie; Kamaluddin, Wahba; Hussaini, Ali (International Journal of Integrated Engineering, 2024)
Flood disasters can occur unexpectedly, causing significant damage to homes or office buildings and their contents. Moreover, they pose a serious threat to health, and the recovery process can take 3-7 days. As a result, many flood victims face challenges in accessing clean water for essential needs, which can be especially difficult in urgent situations. There is a pressing need for solutions that can improve and support flood victims. This project aims to address this need by proposing a system for recycling floodwater. It also seeks to highlight the potential usefulness of floodwater for various purposes. The project utilizes the ADDIE model to develop a tool, specifically a smart indicator called ArduPoSt, which utilizes Arduino technology in conjunction with potassium alum and river stone to monitor and enhance the quality of floodwater. The product was tested with two samples, potassium alum with and without river stone, to gauge the accuracy of water turbidity measurement. The results demonstrated that water turbidity measurement was more accurate and faster when river stones were included. This product is designed to be flexible and valuable for addressing urgent needs of flood victims. Additionally, there are plans to further enhance its usability through the development of a more interactive design with mobile applications in future iterations.